Importance of amino acid composition to improve skin collagen protein synthesis rates in UV-irradiated mice - Murakami, Hitoshi (Springer Vienna, 2011)
Skin collagen metabolism abnormalities induced by ultraviolet (UV) radiation are the major causes of skin photoaging. It has been shown that the one-time exposure of UV irradiation decreases procollagen mRNA expression in dermis and that chronic UV irradiation decreases collagen amounts and induces wrinkle formation. Amino acids are generally known to regulate protein metabolism. Therefore, we investigated the effects of UV irradiation and various orally administered amino acids on skin collagen synthesis rates. Groups of 4–5 male, 8-week-old HR-1 hairless mice were irradiated with UVB (66 mJ/cm(2)) twice every other day, then fasted for 16 h. The fractional synthesis rate (FSR; %/h) of skin tropocollagen was evaluated by incorporating l-[ring-(2)H(5)]-phenylalanine. We confirmed that the FSR of dermal tropocollagen decreased after UVB irradiation. The FSR of dermal tropocollagen was measured 30 min after a single oral administration of amino acids (1 g/kg) to groups of 5–16 UVB-irradiated mice. Branched-chain amino acids (BCAA, 1.34 ± 0.32), arginine (Arg, 1.66 ± 0.39), glutamine (Gln, 1.75 ± 0.60), and proline (Pro, 1.48 ± 0.26) did not increase the FSR of skin tropocollagen compared with distilled water, which was used as a control (1.56 ± 0.30). However, essential amino acids mixtures (BCAA + Arg + Gln, BCAA + Gln, and BCAA + Pro) significantly increased the FSR (2.07 ± 0.58, 2.04 ± 0.54, 2.01 ± 0.50 and 2.07 ± 0.59, respectively). This result suggests that combinations of BCAA and glutamine or proline are important for restoring dermal collagen protein synthesis impaired by UV irradiation.